JAMINAN PRODUK HALAL BAGI PERLINDUNGAN KONSUMEN TELAAH RUUJPH (RANCANGAN UNDANG-UNDANG JAMINAN PRODUK HALAL) DALAM PERSPEKTIF HUKUM EKONOMI ISLAM - Fathimah, Ema; Zailia, Siti (Program Studi Muamalah Fakultas Syariah dan Hukum, 2017)
Indonesia the most populous to-5 as well as the largest Muslim population is a potential market opportunities for the consumption of food products, medicines and cosmetics for the businesses of their own country and from abroad. A transaction from interactions between businesses and consumers is not everything went smoothly but many violations committed by both sides, by both businesses and consumers, but in reality there are a lot more problems that harm consumers.